2017
DOI: 10.1016/j.apenergy.2017.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Synergies between energy supply networks

Abstract: The increasing share of variable renewable energy sources, strict targets set for the reduction of greenhouse gas emissions and the requirements on improvement of system security and reliability are calling for important changes in our energy systems. Energy systems have been in transition, extending their boundaries beyond the energy systems themselves, the 3-D interactive extensions, that relate to the dimensions of physical Space, Time scale and Human behaviors – STH extension. Under the new circumstance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The features of interest include the close entanglement between the two networks, the heterogeneous regional disparity of water and energy resources, as the significant contrast in the economic and environmental performance of various technologies, discussed earlier. Wu and Yan [61] highlighted that the transition of existing fossil-driven energy infrastructure to new low carbon technologies has increased the interactions and coupling of energy supply chains. Antonelli et al [62] using a demonstrating example of the Italian power network, argued that intermittencies of renewable power intensified by demand uncertainty, require careful policymaking regarding the maximum share of renewable energy systems.…”
Section: Methods For Addressing the Water-electricity Nexusmentioning
confidence: 99%
“…The features of interest include the close entanglement between the two networks, the heterogeneous regional disparity of water and energy resources, as the significant contrast in the economic and environmental performance of various technologies, discussed earlier. Wu and Yan [61] highlighted that the transition of existing fossil-driven energy infrastructure to new low carbon technologies has increased the interactions and coupling of energy supply chains. Antonelli et al [62] using a demonstrating example of the Italian power network, argued that intermittencies of renewable power intensified by demand uncertainty, require careful policymaking regarding the maximum share of renewable energy systems.…”
Section: Methods For Addressing the Water-electricity Nexusmentioning
confidence: 99%
“…A fast CO 2 reduction in other sectors is also required [1]. This represents an opportunity to exploit the synergies of sector coupling [2][3][4]. In this study, we investigate the decarbonisation of coupled electricity and reach similar configurations, e.g., heat pumps converting electricity into heat, and district heating systems fed with Combined Heat and Power (CHP) plants are the key-enabling technologies to decarbonise the heating sector efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding greenhouse gas emissions, electricity and low-temperature heating accounted for 1066 Mt and 556 Mt of CO 2 emissions respectively [6]. Previous energy models applied to different regions [2,3,[7][8][9] have shown that imposing a strong CO 2 constraint leads to high Variable Renewable Energy Sources (VRES) penetrations combined with a high-efficiency sector-coupled energy system, referred to as 'Smart Energy System' by Lund and coauthors [4,8]. For instance, under a 95% CO 2 reduction constraint relative to 1990 in Europe [10], energy modelling approaches based on scenario comparison [8] or cost optimisation [2]…”
mentioning
confidence: 99%
“…However, there are several drivers for integrated planning and operation of energy networks including reduction of the use of primary energy, increasing integration of Renewable Energy Resources (RESs) and facilitating a low carbon economy [3]. The synergies between energy networks [4,5] and the interdependencies and interactions between these networks have been shown to have the potential to bring several benefits to the integrated planning, optimal dispatch and operation of energy networks including increasing energy conversion efficiency, maximised utilisation of primary energy sources, improving the energy system flexibility, resilience and security and carbon emission reduction [3,6,7]. Modelling of IES is crucial for understanding the energy networks and the potential benefits of their integrated operation.…”
Section: Introductionmentioning
confidence: 99%